The concept of a prose poem in contemporary Arab criticism (study in cash cash) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research attempts to discuss the concept of the prose poem, and to determine what it is that is difficult to capture, its problematic that has been raised, and the reasons for controversy around it as it is an experimental form that does not settle in any case. He has rebelled against the traditional pattern of poetic writing, radically bypassing the innovation that free poetry brought, and relied on both demolition and construction, and in this concept, the prose poem appears free from all prior intimidation, as the law has fallen into disarray and its creation is in ways that are not. The inner poet and reconstructing it according to the data of his experience.The research attempted to discuss critical opinions that dealt with the emergence of the prose poem, the dialectic of its rejection and acceptance, and the most important issues related to its essence in form and content, and to capture what distinguishes it from other literary genres whose artistic characteristics were - in the majority of which the poem was scattered - the characteristics of which crystallized the forms of birth. In contemporary criticism, which limits it to an aesthetic value, with an interest in addressing the deep relationship between poetic and aesthetic to define an integrated concept of the poetics of the prose poem.The research will follow the descriptive approach, which is concerned with describing concepts, investigating their general lines and discussing them, to reach conclusions that hope to provide usefulness about this problematic experimental form, and what it is.